2018
DOI: 10.1177/1055665618778400
|View full text |Cite
|
Sign up to set email alerts
|

A Single Lab Test to Aid Pierre Robin Sequence Severity Diagnosis

Abstract: A simple CBG heel stick may better predict the physiologic effects of obstructive apnea; therefore, it should be added to the algorithm of PRS workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…These characteristics were (1) M aximum CO 2 > 62 mm Hg; (2) AH I > 23; (3) O 2 S aturation nadir < 79.4%; and (4) T otal sleep time with < 90% O 2 saturation of > 5.7%. Interestingly, Fahradyan et al 19 found higher levels of carbon dioxide (pCO 2 ) through a heel stick capillary blood gas to better “predict” surgical intervention than PSG, using similar ROC analyses. Both studies suffer from similar methodological problems that inherently stem from identifying predictors for surgery ex post facto, as these “predictors” likely influenced the clinical decision to proceed with surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics were (1) M aximum CO 2 > 62 mm Hg; (2) AH I > 23; (3) O 2 S aturation nadir < 79.4%; and (4) T otal sleep time with < 90% O 2 saturation of > 5.7%. Interestingly, Fahradyan et al 19 found higher levels of carbon dioxide (pCO 2 ) through a heel stick capillary blood gas to better “predict” surgical intervention than PSG, using similar ROC analyses. Both studies suffer from similar methodological problems that inherently stem from identifying predictors for surgery ex post facto, as these “predictors” likely influenced the clinical decision to proceed with surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe capillary blood gas CO 2 may be predict the need for a surgical airway. Fahradyan et al (2019) reported the use of CBG CO 2 in 73 patients with RS and stated that ROC curves with cutoff value of pCO 2 level of 49.5 is the best among other variables in terms of specificity and sensitivity combination as an “indication” for surgical intervention. Kwan et al (2021) also noted that a PCO 2 cutoff of 55 mmHg (sensitivity = 55.7%; specificity = 91.3%; area under the curve = 0.78) and a HCO 3 cutoff of 30 mEq/L (sensitivity = 56.2%; specificity = 95.0%; area under the curve = 0.80) were most predictive of patients who “required” a surgical airway.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these techniques have been criticized as subjective or nonstandardized; moreover, not every institution has resources available for obtaining accurate PSG data on newborns. 5,6 Normative values for neonatal PSG are still debated, and PSG, which assesses for airway obstruction during sleep alone, may overlook dynamic airway obstruction which manifests during periods of activity. 7,8 One of the objective parameters measured by PSG is end-tidal carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…Current management algorithms for airway obstruction in infants with RS may incorporate physical examination findings, data related to oral intake (feeding curve), and polysomnography (PSG) findings to quantify the degree of obstruction present and identify surgical candidates. However, some of these techniques have been criticized as subjective or nonstandardized; moreover, not every institution has resources available for obtaining accurate PSG data on newborns 5,6 . Normative values for neonatal PSG are still debated, and PSG, which assesses for airway obstruction during sleep alone, may overlook dynamic airway obstruction which manifests during periods of activity 7,8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation